Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang Sayuran Buah di Pasar Batu Merah Kota Ambon - Sarsin, Abdul; Thenu, Stephen F W; Parera, Weldemina B (Universitas Pattimura, 2025)
The merchants’ welfare can be achieved if the income that the merchants earn is large, because the higher the income is, the higher the profit that is made, so the merchants’ welfare increases day by day. This study aimed to determine the factors that affect the income of fruit and vegetable vendors in the Batumerah market in Ambon City. This study uses a descriptive quantitative method with the research location at the Batumerah Market, Ambon City. The sampling technique was based on Purposive sampling, so the respondents used were 30 fruit and vegetable traders. Data collection uses observation and interviews. Multiple linear regression analysis using SPSS 26 programme was used for data analysis. The findings of this study are: a) Capital has a negative but insignificant effect on the income of fruit and vegetable vendors in Batumerah market, Ambon City. b) The duration of the business operation has a positive but non-significant effect on the income of fruit and vegetable vendors in the Batumerah market in Ambon City, Batumerah. c) Trading time has a negative but non-significant effect on the income of fruit and vegetable vendors in Batumerah market, Ambon City. d) Trading location has a positive but insignificant effect on the income of fruit and vegetable vendors at the Batumerah market, Ambon City. e) Quantity significantly affects the income of fruit and vegetable vendors in the Batumerah market in Ambon City, Batumerah. f) Price has a positive but insignificant effect on the income of fruit and vegetable vendors in Batumerah market, Ambon City. The regression equation obtained is Y = 8.819 - 0.230X1 + 0.071X2 - 0.090X3 + 0.132X4 + 1.044X5 + 0.127X6.